The Association between Antihypertensive Medication Use and Blood Pressure Is Influenced by Obesity - Jash S. Parikh; Arshdeep K. Randhawa; Sean Wharton; Heather Edgell; Jennifer L. Kuk (Hindawi Limited, 2018)
Introduction. One in three US adults is living with obesity or hypertension, and more than 75% of hypertensive individuals are using antihypertensive medications. Therefore, it is important to examine blood pressure (BP) differences in populations that are using these medications with differing obesity status. Aim. We examined whether BP attained when using various antihypertensive medications varies amongst different body mass index (BMI) categories and whether antihypertensive medication use is associated with differences in other metabolic risk factors, independent of BMI. Methods. Adults with hypertension from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2014 were used (n=15,285). Linear regression analyses were used to examine the main effects and interaction between antihypertensive use and BMI. Results. In general, users of antihypertensive medications had lower BP than those not taking BP medications (NoBPMed) (P<0.05), whereby in women, the differences in systolic BP between angiotensin-converting-enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) users and NoBPMed were greater in those with obesity (ACE inhibitors: −14 ± 1 mmHg; ARB: −16 ± 1 mmHg) compared to normal weight individuals (ACE inhibitors: −9 ± 1 mmHg; ARB: −11 ± 1 mmHg) (P<0.05). Diastolic BP differences between women ARB users and NoBPMed were also greatest in obesity (−5 ± 1 mmHg) (P<0.05) whilst there were no differences in normal weight individuals (−1 ± 1 mmHg) (P>0.05). Furthermore, glucose levels and waist circumference in women were higher in those using ACE inhibitors compared to diuretics (P<0.05). Conclusion. ACE inhibitors and ARBs may be associated with more beneficial BP profiles in women with obesity, with no obesity-related BP differences for antihypertensive medication in men. However, there could be potential cardiometabolic effects for some antihypertensive medications that should be explored further.